Clinical diagnosis of ventilator associated pneumonia revisited: comparative validation using immediate post-mortem lung biopsies. Issue 10 (1st October 1999) - Fàbregas, Neus; Ewig, Santiago; Torres, Antoni; El-Ebiary, Mustafa; Ramirez, Josep; de la Bellacasa, Jorge Puig; Bauer, Torsten; Cabello, Hernan
Abstract : BACKGROUND: A study was undertaken to assess the diagnostic value of different clinical criteria and the impact of microbiological testing on the accuracy of clinical diagnosis of suspected ventilator associated pneumonia (VAP). METHODS: Twenty five deceased mechanically ventilated patients were studied prospectively. Immediately after death, multiple bilateral lung biopsy specimens (16 specimens/patient) were obtained for histological examination and quantitative lung cultures. The presence of both histological pneumonia and positive lung cultures was used as a reference test. RESULTS: The presence of infiltrates on the chest radiograph and two of three clinical criteria (leucocytosis, purulent secretions, fever) had a sensitivity of 69% and a specificity of 75%; the corresponding numbers for the clinical pulmonary infection score (CPIS) were 77% and 42%. Non-invasive as well as invasive sampling techniques had comparable values. The combination of all techniques achieved a sensitivity of 85% and a specificity of 50%, and these values remained virtually unchanged despite the presence of previous treatment with antibiotics. When microbiological results were added to clinical criteria, adequate diagnoses originating from microbiological results which might have corrected false positive and false negative clinical judgements (n = 5) were countered by a similar proportion of inadequate diagnoses (n = 6). CONCLUSIONS: Clinical criteria had reasonable diagnostic values. CPIS was not superior to conventional clinical criteria. Non-invasive and invasive sampling techniques had diagnostic values comparable to clinical criteria. An algorithm guiding antibiotic treatment exclusively by microbiological results does not increase the overall diagnostic accuracy and carries the risk of undertreatment.